2019
DOI: 10.1186/s12931-019-1235-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of key clinical features for achieving complete remission in stage III and IV non-small cell lung cancer patients

Abstract: BackgroundAlthough development of immune checkpoint inhibitors and various molecular target agents has extended overall survival time (OS) in advanced non-small cell lung cancer (NSCLC), a complete cure remains rare. We aimed to identify features and treatment modalities of complete remission (CR) cases in stages III and IV NSCLC by analyzing long-term survivors whose OS exceeded 3 years.MethodsFrom our hospital database, 1,699 patients, registered as lung cancer between 1st Mar 2004 and 30th Apr 2011, were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Only Stage IV (not III) was associated with reduced odds of achieving CR (AOR = 0.34). These findings confirm a well-established relationship between advanced NSCLC stage and poorer survival [19][20].…”
Section: Variablessupporting
confidence: 87%
“…Only Stage IV (not III) was associated with reduced odds of achieving CR (AOR = 0.34). These findings confirm a well-established relationship between advanced NSCLC stage and poorer survival [19][20].…”
Section: Variablessupporting
confidence: 87%
“…Recently, Immunotherapy has altered the treatment landscape of late stage NSCLC patients and brought a new perspective to the application of surgery in Stage III patients. Immunotherapy alone or combined with chemotherapy has been shown to improve the overall survival of unresectable NSCLC patients ( 18 ). Therefore, as immunotherapy is being used in advanced NSCLC patients, neoadjuvant Immuno-chemotherapy is being evaluated in Stage III patients.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, Aoki et al reported that 80% of patients diagnosed with stage IV lung cancer but achieved complete remission received local radical therapy such as surgery or radiation during treatment, though this complete remission does not directly mean improving their survival. 18 This suggests that radical local therapy as a part of comprehensive multimodal treatment could benefit selected patients with stage IV lung cancer to achieve complete remission. In the present case, there was a small size of residual alive tumors in a surgical specimen of primary tumor and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al also reported a few similar long-term survivors without cancer treatment in patients with stage IV lung cancer. 18 Additionally, several studies reported the effectiveness of hyperthermic intrathoracic chemotherapy (HITHOC) that it can control the symptoms and prolong the survival of patients with MPE. 34 Surgery combined with HITHOC has been recently reported to be an effective surgical intervention for selected pM1a patients to prolong life expectancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation